The Effect of Tax, Audit Quality and Multinationality on Transfer Pricing - Ambarita, Dinar; Gibtiyyah, Riska Mariyatul; Ibrohim, Ibrohim (Politeknik Siber Cerdika Internasional, 2024)
This study was made with the aim of analyzing the effect of Tax, Audit Quality, and Multinationality on Transfer Pricing. This research was conducted by analyzing the financial statements of multinational companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022. The samples used in this study were 19 multinational companies listed on the Indonesia Stock Exchange during the period 2018 to 2022 using purposive sampling technique. The data used in this study are secondary data in the form of financial reports from each company that has been sampled. The variables used in this study consist of the first independent variable, Tax (X1), the second independent variable, Audit Quality (X2), and the third variable, Multinationality (X3), and Transfer Pricing (Y) as the dependent variable. Panel data regression method is used as the research methodology in this study. Analysis of research results using Eviews 10 Student Version Lite software. The result shows that the best model is Fixed Effect Model (FEM). The results show that Tax and Audit Quality partially affect Transfer Pricing, but Multinationality does not partially affect Transfer Pricing, and simultaneously Tax, Audit Quality, and Multinationality affect Transfer Pricing.